Nucleotide sequences of the 5.8S rRNAs of a mollusc and a porifer, and considerations regarding the secondary structure of 5.8S rRNA and its interaction with 28S rRNA. - Ursi, D (1983)
We report the primary structures of the 5.8 S ribosomal RNAs isolated from the sponge Hymeniacidon sanguinea and the snail Arion rufus. We had previously proposed (Ursi et al., Nucl. Acids Res. 10, 3517-3530 (1982)) a secondary structure model on the basis of a comparison of twelve 5.8 S RNA sequences then known, and a matching model for the interaction of 5.8 S RNA with 26 S RNA in yeast. Here we show that the secondary structure model can be extended to the 25 sequences presently available, and that the interaction model can be extended to the binding of 5.8 S RNA to the 5'-terminal domain of 28 S (26 S) RNA in three species.